The Influence of Good Corporate Governance on Financial Performance Through Corporate Social Responsibility - Andi Jenni Indriakati; Rosnaini Daga (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study examines and determines the effect of good corporate governance on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange through Corporate Social Responsibility. This research is quantitative research with a descriptive statistical approach. The population in this study are manufacturing companies in the food and beverage sub-sector and 28 companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Determined the sample using purposive sampling and obtained a total sample of 23 companies. The data source of this research is secondary data in the form of annual financial reports of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the period 2019-2021. The data analysis method used is descriptive statistical analysis, classical assumption test consisting of (test normality test, heteroscedasticity test, multicollinearity test) and testing all hypotheses through the partial test, simultaneous test, and coefficient of determination test with the help of Eviews tool. The results show that Good Corporate Governance has no significant effect on manufacturing companies' financial performance on the Indonesia Stock Exchange. Corporate Social Responsibility significantly influences the financial performance of manufacturing companies listed on the Indonesia Stock Exchange. Corporate Social Responsibility has a significant effect on moderating the relationship between Good Corporate Governance and the financial performance of manufacturing companies listed on the Indonesia Stock Exchange.